Persepsi Pengguna terhadap Manajemen Layanan Perpustakaan UIN Madura: Evaluasi Tata Kelola dan Prosedur Pelayanan - Alifah Hani Nur Fatimah; Aliyul Karror; Alfin Fahmi; Rusdiana Navlia (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
University libraries play a strategic role in supporting academic learning and research. This study aims to evaluate user perceptions of library service management at UIN Madura, focusing on five key dimensions: clarity of service information, effectiveness of staff coordination, organizational structure support, simplicity of service procedures, and consistency of orientation for new users. The study used a quantitative approach with a survey method. Data were collected through an online Google Form-based questionnaire distributed to active UIN Madura students from various study programs, resulting in 21 valid respondents from diverse academic backgrounds. Data analysis was conducted descriptively using frequency distribution and percentages. The results indicate that user perceptions of library governance are generally quite positive. The majority of respondents gave good ratings to the clarity of service information (85.7% agreed or strongly agreed), the effectiveness of staff coordination (81%), and the organizational structure support (90.5%). However, the new user orientation dimension received the lowest rating, with 23.8% of respondents disagreeing or strongly disagreeing. These findings indicate the need for a more systematic and sustainable strengthening of the library orientation program. Overall, the service management and governance of the UIN Madura library were assessed as quite good. However, improvements are still needed in the aspects of socialization and guidance for new users so that this university library service can function optimally in supporting the academic community.